Developing a PC- and SMS-μC-based stepper motor drive set - (:unkn) unknown (My University, 2008)
This paper describes a PC- and SMS-μC-based Stepper Motor Drive set developed at Marmara University for use in graduate and undergraduate studies. The drive set presents an environment utilizing GSM service, in which students implement stepper motor real-time driving applications, readily get familiar with short message service SMS AT commands with an interface program and team driving fundamentals through an animation program. Additionally, they can develop and implement different driving algorithms for the stepper motors in this environment. © 2008 TEMPUS Publications.
Keywords: GSM; PC- and SMS-μC-based stepper motor drive; SMS AT commands